Association of polymorphisms in the Interleukin 23 receptor gene with osteonecrosis of femoral head in Korean population - Kim, Tae-Ho; Hong, Jung Min; Oh, Bermseok; Cho, Yoon Shin; Lee, Jong-Young; Kim, Hyung-Lae; Lee, Jong-Eun; Ha, Mi-Hyun; Park, Eui Kyun; Kim, Shin-Yoon (Experimental & molecular medicine, 2008)
Osteonecrosis of the femoral head (ONFH) is known as death of the cellular portion of the femoral head due to an interruption in the vascular supply. The underlying pathophysiology regarding bone cell death remains uncertain. Recently, several studies have shown that autoimmune disorders were related to the development of osteonecrosis. This study investigated the genetic effects of Interleukin 23 receptor ( IL23R ) polymorphisms regarding the risk of ONFH. Ten SNPs were selected and genotyped in 443 ONFH patients and 273 control subjects in order to perform the genetic association analysis. It was found that polymorphisms of the IL23R gene (rs4655686, rs1569922 and rs7539625) were significantly associated with an increased risk of ONFH ( P values; 0.0198-0.0447, OR; 1.30-1.49). Particularly, a stratified analysis based on etiology (alcohol, steroid or idiopathic) showed that the associations between these polymorphisms and ONFH were most significant in idiopathic ONFH patients ( P values; 0.0001-0.0150, OR; 1.45-2.17). These results suggest that IL23R polymorphisms may play an important role in the development of ONFH.